PARTISIPASI PETANI ANGGOTA GAPOKTAN DALAM PROGRAM PENGEMBANGAN USAHA PANGAN USAHA PANGAN MASYARAKAT (PUPM) DI DESA MANCASAN KECAMATAN BAKI KABUPATEN SUKOHARJO - Rochana Apriyanti; Suminah Suminah; Emi Widiyanti (AGRITEXTS: Journal of Agricultural Extension, 2018)
The research aimed to investigate the characteristics of farmer gapoktan member which consist of influential factor-factor of program PUPM receiver, to investigate the participation of gapoktan member in PUPM program at stage of planning, implementing, utilizing the result and evaluating and investigating the influence of gapoktan member characteristics which consist of internal and external factor towards participation level of gapoktan member in PUPM. The location of the research was intentionally determined because Mancasan Village is the only village which receives PUPM in year of 2016 in Sukoharjo Regency. The method of sample taking was done randomly using proportional random sampling by the number of sample is 50 people. The data analysis used double linier regression. The result of the research showed that: (1) non formal education, income, land area and organization culture   has   significantly   influenced   towards   the   level   of   gapoktan   member participation whereas other factor such as member’s liveliness, group management, and government role doesn’t influence significantly towards the level of gapoktan member participation  in PUPM program, (2) low  category  factors which  influence gapoktan member participation such as non-formal education and income, fair category member’s liveliness, very low category of land area, well category of management group, culture organization, and government role, (3) farmer gapoktan member participation at stage of planning and utilizing the result categorized fair enough while at stage of planning categorized very low and at stage of evaluating categorized low.